LIMA to LAD grafting returns patient survival to age-matched population: 20-year outcomes of MIDCAB surgery. (21st September 2022) - Manuel, Lucy; Fong, Laura S; Betts, Kim; Bassin, Levi; Wolfenden, Hugh
Abstract: OBJECTIVES: Previous studies have demonstrated the safety and excellent short-term and mid-term survival after minimally invasive direct coronary artery bypass (MIDCAB). We reviewed the long-term outcomes up to 20 years, including overall survival and freedom from reintervention. METHODS: Consecutive patients who underwent MIDCAB between February 1997 and August 2020 were identified. Demographic details, operative information and long-term outcomes were obtained. The Australian National Death Index database was accessed to obtain long-term mortality data. RESULTS: A total of 271 patients underwent an MIDCAB procedure during the study period. There were no intraoperative deaths and only one 30-day mortality (0.4%). The mean length of follow-up was 9.82 ±  8.08 years. Overall survival at 5-, 10-, 15- and 20-year survival was 91.9%, 84.7%, 71.3% and 56.5%, respectively. Patients with single-vessel disease [left anterior descending artery (LAD) only] had significantly better survival compared to patients with multivessel disease ( P  = 0.0035). During long-term follow-up, there were no patients who required repeat revascularization of the LAD territory. Sixty-nine patients died with the cause of death in 15 patients (21.7%) being attributable to ischaemic heart disease. An analysis comparing the isolated LAD disease MIDCAB cohort survival with the expected survival among an age/gender/year matched sample of the Australian reference population, using the standardized mortality ratio, demonstrated that the rate of survival returned to that of the reference population (standardized mortality ratio = 0.94). CONCLUSIONS: MIDCAB is a safe and effective revascularization strategy which can be successfully performed in a carefully selected patient population with low morbidity and excellent long-term results. The survival of MIDCAB patients returns to that of their age/gender/year-matched counterparts within the normal population and hence should be offered as an alternative to coronary stenting when counselling patients with ischaemic heart disease. Abstract : Coronary artery bypass grafting (CABG) remains the gold standard treatment for complex multivessel coronary artery disease, resulting in superior long-term symptom relief and improved survival when compared to medical therapy and percutaneous coronary intervention (PCI) [1, 2].